Pressure-induced electrical and structural anomalies in Pb1-xCaxTiO3 thin films grown at various oxygen pressures by chemical solution route - Pontes, Fenelon Martinho Lima [UNESP]; Galhiane, Mario Sergio [UNESP]; Santos, Lucidio de Sousa [UNESP]; Rissato, Sandra Regina [UNESP]; Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Leite, E. R.; Chiquito, A. J.; Pizani, P. S.; Jardim, R. F.; Escote, M. T. (Iop Publishing Ltd, 2008)
Lead calcium titanate (Pb1-xCaxTiO3 or PCT) thin films have been thermally treated under different oxygen pressures, 10, 40 and 80 bar, by using the so-called chemical solution deposition method. The structural, morphological, dielectric and ferroelectric properties were characterized by x-ray diffraction, FT-infrared and Raman spectroscopy, atomic force microscopy and polarization-electric-field hysteresis loop measurements. By annealing at a controlled pressure of around 10 and 40 bar, well-crystallized PCT thin films were successfully prepared. For the sample submitted to 80 bar, the x-ray diffraction, Fourier transformed-infrared and Raman data indicated deviation from the tetragonal symmetry. The most interesting feature in the Raman spectra is the occurrence of intense vibrational modes at frequencies of around 747 and 820 cm(-1), whose presence depends strongly on the amount of the pyrochlore phase. In addition, the Raman spectrum indicates the presence of symmetry-breaking disorder, which would be expected for an amorphous (disorder) and mixed pyrochlore-perovskite phase. During the high-pressure annealing process, the crystallinity and the grain size of the annealed film decreased. This process effectively suppressed both the dielectric and ferroelectric behaviour. Ferroelectric hysteresis loop measurements performed on these PCT films exhibited a clear decrease in the remanent polarization with increasing oxygen pressure.